Trabalho em condições análogas ao de escravo: uma análise a partir da jurisprudência do TRF 3ª da Região - FREITAS, Luiza Cristina de Albuquerque (Universidade Federal do Pará, 2018)
This study was developmented with the objective of verify how the TRF of the 3rd Region has been interpreted and applied the crime described in art. 149 of the Criminal Code. For that, was realized a doctrinal study was carried out on the concept of contemporary slave labor in Brazil and yours respective executive modalities. Also been investigated as interpretive currents about to the issue. The field research was carried out from the TRF's jurisprudence of the 3rd Region, be realized an investigative study was carried out on the characterization of slave labor and the elements that is used by TRF inside the cases that are submitted. The method used was the Deductive Method there was based on the analysis of the information obtained in the field research, confronted with the theoretical arguments and with the legal norms, as from an logical reasoning in order to reach the conclusion of the question proposed. The results showed that the TRF of the 3 rd Region, interpret the concept of slave work based on the protection of the dignity of the human person, in a way unrelated to the restriction of the freedom of locomotion. However, in spite of a high incidence of convictions in this court, it was found that the definitive criminal penalty is fixed, in low magnitude in most cases, and, for this has been replaced anothers criminal penaltys so much soft, thare have no condicions to repress sufficiently and appropriately the criminals.